Constraint preserving mapping algorithm for XML storage - Ahmad, Kamsuriah; Mamat, Ali; Ibrahim, Hamidah; Mohd Noah, Shahrul Azman (2006)
The use of XML as the common format for representing, exchanging, storing, integrating and accessing data poses many new challenges to database systems. Most of application data are stored in relational databases due to its popularity and rich development experiences over it. Therefore, how to provide a proper mapping approach from XML model to relational model becomes the major research problem. The mapping from XML to relational is not an easy task because the data model of an XML document is fundamentally different from that of a relational database. Especially the structure of an XML document is hierarchy and the XML elements may be nested and repeated. So it is also useful in information exchange and data integration for preserving the semantics of data originating in XML to relational databases. Although several approaches exist, they are incomplete in the sense that they focus only on a part of constraints and ignore the constraints for XML as expressed in functional dependencies. In this paper, we propose an algorithm how to preserve these constraints while mapping from XML to relational schema. Compared with other methods, our approach can preserve more XML constraints, while reduced nesting and redundant data.